The design and construction of a flying bird robot - Bensch, Marius (Department of Electrical Engineering, 2014)
The purpose of this project is to investigate the issues surrounding the design and construction of a flying bird robot. The ideal would be to re-create a model of a bird that looks like bird, functions like a bird with regard to the biomechanical issues involved in flight and uses control systems that emulate the ones used by the bird to control the flight path.